Bimodal oxidation : coupling of heterogeneous and homogeneous reactions - Bakhtchadjian, Robert (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
This book is devoted to the problems of oxidation chemical reactions and addresses bimodal reaction sequences. Chemical reactions of oxidation, occurring under certain conditions and in multicomponent systems are complex processes. The process of the oxidation essentially changes in the presence and contact of the solid substances with reactants. The role of solid substances and the appearance of this phenomenon in oxidation reaction are discussed. The reader will understand the "driving forces" of this phenomenon and apply it in practice. Written for chemists, physicists, biologists and engineers working in the domain of oxidation reactions. Key Selling Features: Covers the historical background, modern state of the art, and perspectives in investigations of the coupling between heterogeneous and homogeneous reactions Discusses the feasible pathways of the coupling of heterogeneous and homogeneous reactions in oxidation in man-made and natural chemical systems Addresses the abundance, peculiarities and mechanisms of the bimodal reaction sequences in oxidation with dioxygen in recent decades Discusses the existence of the bimodal reaction sequences in chemical systems investigations in atmospheric chemistry and heterogeneous photocatalysis Presented in a simple concise style, accessible for both specialists and non-specialists
OCLC-licensed vendor bibliographic record.
Keywords: Oxidation; Heterogeneous catalysis; Homogeneous catalysis; SCIENCE / Chemistry / General; SCIENCE / Chemistry / Physical & Theoretical; SCIENCE / Chemistry / Industrial & Technical